2021
DOI: 10.21037/jtd-2020-mics-12
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive cardiac surgery—a Fad or the Future?

Abstract: Editorial on Minimally Invasive Cardiac SurgeryMinimally invasive cardiac surgery-a Fad or the Future?Over recent years there has been significant progress in the development and adoption of minimally invasive techniques in cardiac surgery (1). In thoracic surgery, video-assisted thoracoscopic surgery (VATS) has become the norm (2). In cardiac surgery, the median sternotomy has been, and remains, the trusted, well-established and gold standard access route for many decades. However, perhaps motivated by develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…A successful MICS programme requires a multidisciplinary approach, requiring involvement from anaesthesiologists, cardiac surgeons, perfusionists, scrub nurses, etc. 21 Myocardial protection plays an essential part in MICS. 4 An ideal cardioplegia solution should minimise myocardial damage, haemodilution, the need for re-dosing, the incidence of arrhythmia on releasing the AXC and cost effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful MICS programme requires a multidisciplinary approach, requiring involvement from anaesthesiologists, cardiac surgeons, perfusionists, scrub nurses, etc. 21 Myocardial protection plays an essential part in MICS. 4 An ideal cardioplegia solution should minimise myocardial damage, haemodilution, the need for re-dosing, the incidence of arrhythmia on releasing the AXC and cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…26 These were promising because one of the major barriers for MICS is the costs associated with the new perfusion and surgical equipment and instruments needed. 21 Savings from the cardioplegia solution can cover the cost for the new equipment. Study by Zanobini and colleagues suggested the combination of minimally invasive approach with CS significantly preserved right ventricular function post-operatively when compared with MS approach.…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart Association defined "minimally invasive" as smaller sternotomy or non-sternotomy strategies aided by robotic or video-assisted technologies [22], and a variety of approaches have been described. Access route is a minor component of invasiveness within cardiac surgery, with cardiopulmonary bypass (CPB), aortic cross clamping, cardioplegic arrest and opening of cardiac chambers contributing more to the invasiveness and risk of complications of the procedure, beyond that of the incision [23]. For the surgical treatment of ASD, minimal-access approaches include partial or mini-sternotomy, right anterolateral thoracotomy, right oblique sub-axillary incision, right vertical sub-axillary incision, right posterior mini-thoracotomy, video-assisted thoracoscopy (VATS)/endoscopic and robotic approaches, with peripheral cannulation for cardiopulmonary bypass.…”
Section: Surgical Closurementioning
confidence: 99%
“…Lately, minimally invasive procedures in cardiac surgery (MICS) are gaining popularity and this poses certain challenges for anesthesiology practice [1]. Minimally invasive direct coronary artery bypass (MIDCAB) being commonly applied subtype of MICS where revascularization takes place through conjunction of the left internal thoracic artery (ITA) and left anterior descending artery, nowadays are implemented worldwide more often [2].…”
Section: Introductionmentioning
confidence: 99%